2016
DOI: 10.1021/acsami.5b12058
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Sensing Using Functionalized Amorphous In–Ga–Zn–O Field-Effect Transistors

Abstract: Recent advances in glucose sensing have focused on the integration of sensors into contact lenses to allow noninvasive continuous glucose monitoring. Current technologies focus primarily on enzyme-based electrochemical sensing which requires multiple nontransparent electrodes to be integrated. Herein, we leverage amorphous indium gallium zinc oxide (IGZO) field-effect transistors (FETs), which have found use in a wide range of display applications and can be made fully transparent. Bottom-gated IGZO-FETs can h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“…The detailed surface functionalization process is described in the Experimental and it was confirmed by XPS analysis (Figures S8 and S9). The functionalization process has been reported and characterized by other researchers, 76 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 4b shows that a device functionalized with boronic acid exhibited a significant decrease (18%) in sensing current upon the addition of a 3 pM glucose solution (in 0.1X PBS). This agrees with the effect of boronate anion-glucose electrostatic gating, which depletes electron carriers at the semiconductor/liquid interface in the n-type In 2 O 3 film.…”
Section: Resultsmentioning
confidence: 98%
“…The detailed surface functionalization process is described in the Experimental and it was confirmed by XPS analysis (Figures S8 and S9). The functionalization process has been reported and characterized by other researchers, 76 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 4b shows that a device functionalized with boronic acid exhibited a significant decrease (18%) in sensing current upon the addition of a 3 pM glucose solution (in 0.1X PBS). This agrees with the effect of boronate anion-glucose electrostatic gating, which depletes electron carriers at the semiconductor/liquid interface in the n-type In 2 O 3 film.…”
Section: Resultsmentioning
confidence: 98%
“…The biosensors on the flexible array are also important because they make real-time monitoring possible by adopting the human body. Various types of biosensor have been investigated [85], and the active-matrix-based sensor array is the key technology for transforming various types of signals into electrical signals, and for analyzing signals. For example, Figure 10 shows a glucosebiosensor embedded on IGZO TFTs, whose transfer characteristics were changed by changing concentration of glucose.…”
Section: Current Development Of the Oxide Tft: Flexible And Stretchabmentioning
confidence: 99%
“…Recently, ZnO NWs-based FET biosensors for glucose detection were reported with enhanced sensing performances. For further advancement in glucose sensing, Du et al (2016) reported bottom-gated indium gallium ZnO (IGZO) FET for noninvasive continuous glucose monitoring and device integration into contact lenses. Yu et al (2013) demonstrated the fabrication of a self-powered, piezotronic effect enhanced glucose sensor based on metal-semiconductor-metal structured single ZnO NW device.…”
Section: Nws-based Fet Biosensormentioning
confidence: 99%